Learning Problems and Neurofibromatosis - J Gordon Millichap (Pediatric Neurology Briefs, 1989)
A group of 32 children with von Recklinghausen’s neurofibromatosis (VRNF) and school learning problems was compared to a matched sample of learning-disordered (LD) students without known genetic or medical disorders at the Division of Psychology, Department of Pediatrics, University of Iowa, Iowa City.